Morphometric, Meristic Characters, And Gonad Mature Level Of Pepudah Fish (Rasbora Lateristriata) From Sokong Rivers, North Lombok District - Ali Harris; Mita Ayu Liliyanti; Luh Gede Sumahiradewi; Novita Tri Artiningrum (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2021)
This study aims to obtain information about the morphological characters (morphometric and meristic) and the maturity level of the gonads of pepudah fish in North Lombok. The data relating to the morphology obtained is expected to be used as basic information in management and cultivation activities in the future. Data collection was carried out in the basic science laboratory of the Faculty of Fisheries, University of 45 Mataram. Morphometric and meristic data were obtained by measuring and calculating the morphological characters present in the pepudah fish and followed by the t-test to see the growth pattern. Gonad maturity data were obtained by comparing the TKG value with the GSI value. The results of the morphological data obtained indicate that the pepudah fish obtained in the Sokong River have a negative allometric growth pattern and are still in their infancy.